Template Synthesis of Linear‐Chain Nanodiamonds Inside Carbon Nanotubes from Bridgehead‐Halogenated Diamantane Precursors. (12th August 2015) - Nakanishi, Yusuke; Omachi, Haruka; Fokina, Natalie A.; Schreiner, Peter R.; Kitaura, Ryo; Dahl, Jeremy E. P.; Carlson, Robert M. K.; Shinohara, Hisanori
Abstract A simple method for the synthesis of linear‐chain diamond‐like nanomaterials, so‐called diamantane polymers, is described. This synthetic approach is primarily based on a template reaction of dihalogen‐substituted diamantane precursors in the hollow cavities of carbon nanotubes. Under high vacuum and in the presence of Fe nanocatalyst particles, the dehalogenated radical intermediates spontaneously form linear polymer chains within the carbon nanotubes. Transmission electron microscopy reveals the formation of well‐aligned linear polymers. We expect that the present template‐based approach will enable the synthesis of a diverse range of linear‐chain polymers by choosing various precursor molecules. The present technique may offer a new strategy for the design and synthesis of one‐dimensional nanomaterials.